2019
DOI: 10.1108/bfj-12-2017-0683
|View full text |Cite
|
Sign up to set email alerts
|

Consumption values and physical activities: consumers’ healthy eating choices

Abstract: Purpose The purpose of this paper is to investigate the extent to which consumption values and physical activities influence consumers’ healthy eating choices. Design/methodology/approach A survey with 292 participants was analysed by means of bilateral factor analysis and structural equation modelling to study the consumers’ healthy eating choices based on consumption values and moderation effect of physical activities. Findings Consumers’ healthy eating choices are strongly linked to epistemic and emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…Thus, advertisements and curiosity stemming from observing others use FDAs can positively impact customers' intentions to order food on FDAs. A positive association between epistemic value and choice behavior was in fact confirmed by Thomé et al (2019). Support for this hypothesis indicates that users are more likely to order food from FDAs if they see their friends and acquaintances do the same.…”
Section: Proposition Of Food Delivery Appsmentioning
confidence: 73%
See 2 more Smart Citations
“…Thus, advertisements and curiosity stemming from observing others use FDAs can positively impact customers' intentions to order food on FDAs. A positive association between epistemic value and choice behavior was in fact confirmed by Thomé et al (2019). Support for this hypothesis indicates that users are more likely to order food from FDAs if they see their friends and acquaintances do the same.…”
Section: Proposition Of Food Delivery Appsmentioning
confidence: 73%
“…Epistemic value denotes the ability of a product or service to incite curiosity, offer a sense of novelty, and/or satisfy information search instincts (Choe and Kim, 2019;Wong et al, 2019). Studies have found a positive association between epistemic value and choice behavior in domains such as health food (Thomé et al, 2019) and tourism destinations (Ashton, 2015). This study measures epistemic value in terms of visibility, which reflects the nature of mobile apps like FDAs.…”
Section: Epistemic Value (Visibility)mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the quality attributes, the therapeutic properties of honey were the most important, as reported by previous studies [25,63]. Several studies, in fact, demonstrated that honey is a product with numerous therapeutic properties for human health that are able to prevent and/or treat certain diseases [64,65] and consumers are more and more conscious about its health and medical benefits [56,66]. This result is consistent with Sacchi et al [67] who highlighted that, nowadays, consumers are increasingly interested in food that provides health benefits by improving well-being and reducing the risk of diseases.…”
Section: Discussionmentioning
confidence: 90%
“…business model “innovations that create positive and/or significantly reduced negative impacts for the environment and/or society” (Bocken et al , 2014, p. 44). These business model innovations for sustainability have aimed to tackle different sustainability-related issues among those that concern the food industry (Cicatiello et al , 2016; El Bilali, 2019; Matzembacher and Meira, 2019; Mirosa et al , 2016; Papargyropoulou et al , 2014; Thomé et al , 2019). Triggered by the recent digital revolution, an increasing number of organizations in the food industry have designed new business models that leverage digital technology to have an environmental or social impact (Ciulli et al , 2019; Michelini et al , 2018).…”
Section: Introductionmentioning
confidence: 99%